Analisis Daya Dukung & Penurunan Bored Pile 80cm di Proyek Kompleks Kantor-Apartemen dengan Metode Analitis & Elemen Hingga - Gusar Tampubolon; Roesyanto Roesyanto; Gina Cynthia R Hasibuan (Jurnal Syntax Admiration, 2024)
This study will look for the ultimate bearing capacity value of bored pile foundation and foundation subsidence, based on SPT data and loading test calculated empirically with SPT data using equations provided by O'Neil and Reese while loading test data using curve interpretation Davidson Method, Mazurkiewich Method, Chin Method and finite element method using 2D Plaxis software with all types of medium mesh. After analysis, the ultimate bored pile carrying capacity value of ø 80 cm based on SPT data using the O'neill and Reese equations was 1242 tons, then analysis using the Davisson method of 875 tons, using the Mazurkiewiech method of 960 tons and the Chin method of 876 tons. While the ultimate carrying capacity based on PLAXIS 2D calculations is 1364 tons. 5. Based on SPT data, the carrying capacity of a single bored pile axial permit (Qi) was obtained at 497 tons with SF = 2.5. And for the value of the decrease that occurs in the bored pile foundation based on analytical results is 22.85 mm, based on the loading test is 7.95 mm and based on the PLAXIS 2D program is 14.12 mm. Based on the results of the analysis, it can be concluded that the O'Neil and Reese equations provide a greater value than the interpretation of load testing so that it will provide a large safety value if used when design and descent analysis that is closest to the results in the field is analysis with 2D PLAXIS with the Mohr-Coulomb modeling type. There are differences in carrying and lowering capacity analysis results with several methods used, but the use of analytical methods and finite element methods with PLAXIS 2D meets the safety requirements of bored pile foundations.